T-lymphoblastic Leukaemia: A Distinct Variant of Acute Leukaemia. Issue 5920 (22nd June 1974) - Catovsky, D.; Goldman, J. M.; Okos, A.; Frisch, B.; Galton, D. A. G.
Abstract : Two cases of acute lymphoblastic leukaemia (A.L.L.) of T-cell type are reported. Clinically they were characterized by very high peripheral blood blast cell counts at presentation, the early development of meningeal leukaemia, and relative resistance to treatment with combination chemotherapy. Leukaemic cells from both patients lacked all the B-cell markers investigated, but 60-65% of their cells formed rosettes with sheep red cells. Cytochemical and surface structure studies helped to define additional features of these cells and confirmed their T-cell nature. It seems that this variant of A.L.L. may not be uncommon and that it can be distinguished on clinical and immunological grounds from the usual type of A.L.L. which runs a less aggressive course and lacks B- or T-cell markers.